Volcanic Rock of Slamet Volcano as the Potential of Soil Ameliorant - Zaenurrohman, Januar Aziz; Qur'an, Mudrik Infithor Nurul; Ismangil, Ismangil; Siswandi, Siswandi; Candra, Adi (Indonesian Journal on Geoscience, 2024)
Mount Slamet is an active volcano in Java Island, Indonesia. Slamet volcanic rocks comprise various igneous and pyroclastic rocks, including basaltic lava, andesitic lava, pyroclastic rocks, and intrusions. Geochemical analysis of rocks in the studied area (301300 mE - 303300 mE and 9189400 mN - 9191400 mN) showed the presence of high calcium and iron elements. This geological study aims to determine the potential of material resources contained to be used for agricultural needs. The potential nutrients to be found such as P, K, Mg, Ca, Fe, Ti, Na, Mn, and Si with a DHL conductivity value of 0.0473 - 0.1318 mmhos /cm are classified as non-salinity, which is safe for soil improvement. Then the neutralization value relative to calcite is between 15.45 - 27.27 %, and the abrasion pH value is between 8.05 - 8.91. The agrogeological analysis shows that the Slamet volcanic rock in Baturraden area has good prospects as an ameliorant for highly weathered (acid) soils.